A testemunha e a memória. O paradoxo do indizível da tortura e o testemunho do desaparecido - Castor M.M. Bartolomé Ruiz (Ciências Sociais Unisinos)
The structural modern violence it¿s related to biopolitcs. On the other side of biopolitic resists the victim as a witness. The victim¿s testimony grows in a new political event that narrates the dark side of the violence, denied by the politics of forgetfulness about the victim and winners. The victim testimony carries the paradox of unspeakable of the suffering. The language, being necessary, is not able to express the totally of the experience of the victim¿s suffering. When is narrated, the testimony leaves an unspeakable violence zone, that paradoxically becomes the essential part of the testimony. The tortured and missed people because of the biopolitic became truly witnesses.